Integrating Path–Goal Leadership and Prophetic Leadership: A SLR of Leadership Models in Contemporary Da'wa - Muhammad Rezky Pratama Marsudi; Cecep Castrawijaya (Islam and Social Sciences Review, 2025)
Contemporary da'wah organizations operate in increasingly complex social and digital environments, requiring leadership models that are adaptive while remaining grounded in Islamic values. Although the Path–Goal leadership theory has been widely applied in organizational studies, its integration with Prophetic leadership within the context of da'wah organizations remains conceptually underexplored. This study aims to develop an integrated leadership framework by synthesizing Path–Goal leadership theory with Prophetic leadership principles for contemporary da'wah organizations. This study employs a Systematic Literature Review (SLR) using a thematic synthesis approach. Relevant national and international scholarly publications on leadership, Islamic leadership, and da'wah management were systematically identified, screened, and analyzed through open coding, thematic categorization, and conceptual synthesis to construct an integrated theoretical framework. The review demonstrates that leadership effectiveness in da'wah organizations cannot be achieved through a single leadership style. Instead, effective leadership emerges from the dynamic integration of four Path–Goal leadership styles directive, supportive, participative, and achievement-oriented leadership with Prophetic leadership values, including trustworthiness (amanah), truthfulness (ṣidq), wisdom (faṭānah), and effective communication (tablīgh). This integrated framework enhances organizational adaptability, strengthens member engagement, supports innovation in digital da'wah, and improves organizational performance while preserving Islamic ethical principles. This study contributes to the literature by proposing a novel conceptual framework that bridges modern leadership theory and Islamic leadership philosophy within da'wah organizations. The synthesis extends the application of Path–Goal leadership theory beyond conventional organizational settings and offers a theoretically grounded reference for future empirical research as well as practical guidance for leadership development in Islamic nonprofit organizations.